Patterns, price and predictors of successful empiric antibiotic therapy in a real‐world setting. (7th February 2021) - Akinosoglou, Karolina; Koutsouri, Christina‐Panagiota; deLastic, Anne‐Lise; Kolosaka, Martha; Davoulos, Christos; Niarou, Vasiliki; Kosmopoulou, Foteini; Ziazias, Dimitrios; Theodoraki, Spyridoula; Gogos, Charalambos
Abstract: What is known and Objective: Prompt and appropriate empiric antibiotic therapy (EAT) remains the cornerstone of successful outcomes, while the majority of blood cultures do not identify pathogen. We aimed to report patterns of EAT and its impact on outcomes and associated medical costs, while exploring predictors of its success in a real‐world setting. Methods: We retrospectively utilized the prospective registry of the medical unit of a tertiary university hospital, including patients admitted with diagnosis of infection between 1st May 2016 and 1st May 2018. Costs of hospitalization and unit of antibiotic regimen were retrieved from a database regarding Greek hospitals containing hospitalization‐cost data for each ICD‐10 code and the national formulary, respectively. Results: A total of 489 patients were included in this study. Mean age was 61.3 years, 53% were males, while intra‐abdominal infections predominated (55%). The most commonly administered EAT included quinolones (48%), followed by piperacillin/tazobactam (18%), or other regimens alone or in combination. EAT was successful in 67% and failed in 33% of cases. Fourteen patients died of the infection before EAT was switched, while among 55 patients that EAT had to be modified, mortality was 22%. Presence of urinary tract infection and use of quinolones, least predicted for failure of EAT [OR:0.15 (0.07–0.35), p  < 0.0001, OR:0.53 (0.32–0.90), p  = 0.019, respectively], in contrast to presence of sepsis [OR:3.11 (1.79–5.40), p  < 0.0001]. Patients with failure had longer length of stay [7(5–11) versus 4 (3–6) days], higher antibiotic [201.9 (97.8–471.8) vs 104.6 (60.2–187.7) euros] and hospitalization costs [1409.3 (945.4–2311.6) vs 759.4 (516.5–1036.5) euros] ( p  < 0.0001). Discussion: We observed significantly increased antibiotic‐related, healthcare‐related costs and length of stay in patients with failure of EAT. Moreover, in our cohort, absence of sepsis, presence of urinary tract infection and use of quinolones better predicted for success of EAT. What is new and Conclusions: Appropriate selection of EAT is crucial to ensure better outcomes and minimize costs. Abstract : Appropriate choice of empiric antibiotic therapy is pivotal to ensure best possible outcomes, but also minimize length of stay and elongate antibiotic and hospitalization related costs.